Change in viral bronchiolitis management in primary care in the UK after the publication of NICE guideline - Carande, E; Cheung, C; Pollard, A; Drysdale, S (BMJ Publishing Group, 2018)
The aim of this study was to investigate changes in General Practitioner (GP) management before and after the publication of the NICE bronchiolitis guideline. In March 2015 and May 2016, an electronic questionnaire was sent to GPs. It was completed by 1001 GPs in 2015 and 1009 in 2016. There were small but significant improvements in proportions of GPs using a guideline, measuring oxygen saturations, and providing written guidance, and appropriate reductions in those prescribing medications. 35% had read the guideline and 25% changed their practice since guideline publication. There were modest but significant improvements in reported management by GPs after guideline publication.